A review of tin disulfide (SnS2) composite electrode materials for supercapacitors. Issue 4 (5th December 2021) - Setayeshmehr, Mahboobeh; Haghighi, Maryam; Mirabbaszadeh, Kavoos
Abstract: The rapid growth of the global economy has substantially increased fossil fuel consumption, which brings about two challenges: the destruction of the existing fossil fuel reserves and the emergence of severe environmental problems, such as climate pollution. Therefore, developing clean energy resources and relevant technologies is an urgent priority. In this regard, the enhancement of energy storage technologies and devices gain paramount importance. Two types of energy storage devices are batteries and supercapacitors. Supercapacitors, especially, double layer supercapacitors and pseudo‐capacitors, have attracted more attention than batteries. They possess better characteristics, such as higher‐power density and longer cycle life‌. Various nanocomposite materials, such as carbon (graphene or carbon nanotubes), metal oxides (sulfide), and conductive polymers, are used in the construction of supercapacitor electrodes. Among these materials, tin (IV) sulfide is the most widely utilized material as its layered structure is capable of forming two‐dimensional morphologies. Owing to its abundance in nature, nontoxicity, and cheapness, tin (IV) sulfide is regarded as a promising material for constructing efficient electrodes. The faradic behavior of this material also makes it suitable for supercapacitor applications. The present review article aims to survey and summarize the findings of the studies on tin (IV) sulfide and its utility as an electrode material in supercapacitors. This article also gives an overview of the solutions proposed to improve the performance of this material in supercapacitors.